Calcium Biofortification: Three Pronged Molecular Approaches for Dissecting Complex Trait of Calcium Nutrition in Finger Millet (Eleusine coracana) for Devising Strategies of Enrichment of Food Crops - Sharma, Divya; Jamra, Gautam; Singh, Uma M.; Sood, Salej; Kumar, Anil (Frontiers in Plant Science, 2017)
Calcium is an essential macronutrient for plants and animals and plays an indispensable role in structure and signalling. Low dietary intake of calcium in humans has been epidemiologically linked to various diseases which can have serious health consequences over time. Major staple food-grains are poor source of calcium however, finger millet [Eleusine coracana (L.) Gaertn.], an orphan crop has an immense potential as a nutritional security crop due to its exceptionally high calcium content. Understanding the existing genetic variation as well as molecular mechanisms underlying the uptake, transport, accumulation of calcium ions (Ca2+) in grains is of utmost importance for development of calcium bio-fortified crops. In this review, we have discussed molecular mechanisms involved in calcium accumulation and transport thoroughly, emphasized the role of molecular breeding, functional genomics and transgenic approaches to understand the intricate mechanism of calcium nutrition in finger millet. The objective is to provide a comprehensive up to date account of molecular mechanisms regulating calcium nutrition and highlight the significance of bio-fortification through identification of potential candidate genes and regulatory elements from finger millet to alleviate calcium malnutrition. Hence, finger millet could be used as a model system for explaining the mechanism of elevated calcium (Ca2+) accumulation in its grains and could pave way for development of nutraceuticals or designer crops.